2013
DOI: 10.1177/0002764213487340
|View full text |Cite
|
Sign up to set email alerts
|

Racism and Health I

Abstract: This article reviews the scientific research that indicates that despite marked declines in public support for negative racial attitudes in the United States, racism, in its multiple forms, remains embedded in American society. The focus of the article is on the review of empirical research that suggests that racism adversely affects the health of non-dominant racial populations in multiple ways. First, institutional racism developed policies and procedures that have reduced access to housing, neighborhood and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
444
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 962 publications
(460 citation statements)
references
References 95 publications
13
444
1
2
Order By: Relevance
“…These findings are in line with several reviews and studies that have consistently suggested that experienced discrimination has a harmful psychological impact on those against whom it is directed (e.g., Brondolo et al, 2009b;Harrell, 2000;Harris et al, 2006: Krieger, 1999Paradies, 2006;Priest et al, 2012;Williams & Mohammed, 2009;2013a;2013b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in line with several reviews and studies that have consistently suggested that experienced discrimination has a harmful psychological impact on those against whom it is directed (e.g., Brondolo et al, 2009b;Harrell, 2000;Harris et al, 2006: Krieger, 1999Paradies, 2006;Priest et al, 2012;Williams & Mohammed, 2009;2013a;2013b).…”
Section: Discussionsupporting
confidence: 90%
“…Numerous review articles have found that racial/ethnic discrimination contributes to variations in health risks within racial and ethnic minorities (Brondolo, Gallo, & Myers, 2009b;Paradies, 2006;Priest et al, 2012;Williams & Mohammed, 2009;2013a;2013b).…”
Section: Racial/ethnic Discrimination and Psychological Well-beingmentioning
confidence: 99%
“…For example, Black men may experience stress vicariously as a result of family and close friends being exposed to race-based and general stressors (Williams & Mohammed, 2013). Neighborhood stressors such as exposure to toxins, violence, and surveillance may also negatively affect Black men's health (Williams, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Scholarship in this area has generally focused on specific discrete and chronic stressors, including discrimination (e.g., major events such as being unfairly fired or denied a promotion; everyday experiences with discrimination such as being treated with less courtesy), chronic strains (e.g., work-family conflict), traumas (e.g., being a victim of or witnessing violence), recent life events (e.g., involuntary job loss), and financial strain (e.g., difficulty paying bills)-showing that each has harmful effects on mental and physical health (Thoits, 2010;Turner, Thomas, & Brown, 2016;Umberson et al, 2016;Williams & Mohammed, 2013). Furthermore, a study by Sternthal, Slopen, & Williams (2011) illustrates the importance of examining the effects of cumulative stress exposure, as well as the collective effects of numerous stressors in order to determine their unique impacts on health.…”
Section: Stressors and Healthmentioning
confidence: 99%
“…Early on, we made clear: ''In attributing disparities to race, we mean the historical legacy of racism in the United States (US) taking shape through various means, including slavery, Jim Crow, and segregation [12]. This legacy involves discrimination which may be intentional or the result of policies, laws or practices that systematically disadvantage blacks and shape economic opportunities [13] (and also) indirect processes whereby blacks are more vulnerable to economic or political shifts because of this legacy'' [14]. The reality of class in the US can reinforce this legacy by mediating access to quality neighborhoods, housing, and education.…”
Section: Introductionmentioning
confidence: 99%